Lingkungan kerja, kompensasi dan disiplin kerja yang berperan dalam memberi perubahan pada kepuasan kerja karyawan - Rosyidanta, Latiefatur Riska; Dewi, Dian Ayu Liana (Nur Science Institute, 2025)
In the face of increasing business competition, companies must ensure both sustainability and growth. Employee job satisfaction plays a pivotal role in maintaining operational stability and long-term performance. This study investigates the influence of work environment, compensation, and work discipline on employee job satisfaction at PT Swadaya Graha, Rembang Regency. A total of 94 employees participated, and data were collected through a structured questionnaire utilizing a Likert scale. The analysis employed multiple linear regression. The results reveal that while the work environment does not significantly affect job satisfaction, compensation, and work discipline have significant positive impacts. The model explains 73.6% of the variance in job satisfaction, indicating that these factors are substantial predictors, while the remaining 21.4% may be attributed to variables outside the scope of this study. These findings offer practical implications for human resource strategies aimed at enhancing employee satisfaction and performance.